Effects of spices mixture and cooking on antioxidant activity in Ethiopian spicy hot red pepper powder - Tadewos Hadero Medalcho; Kebede Abegaz Ali; Engeda Dessalegn Augchew (Scientific Reports)
Abstract In Ethiopia, spicy hot red pepper, locally known as berbere, is a common food additive that is consumed in a variety of forms, which have high antioxidant potentials. The antioxidant activity of selected spices, such as garlic, ginger, cardamom, and black cumin, and hot red pepper (HRP) as well as both raw and cooked experimental and commercial spicy hot red pepper were evaluated using 2, 2-diphenyl-1-picrylhydrazyl (DPPH), 2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), ferric ion (Fe3+) reducing antioxidant power (FRAP), and ferrous ion (Fe2+) chelating activity (FICA) assays. The IC50 of DPPH and ABTS of garlic were the lowest of all selected spices; conversely, they had the strongest free radical scavenging activities. The FRAP of ginger, and FICA of garlic were the strongest of all selected spices. The antioxidant potential of raw experimental (ESP), and commercial (CSP) spicy hot red pepper were stronger than the plain spices; however, cooked commercial spicy HRP or sauté (CSS) was the strongest of all following uncooked commercial spicy HRP (CSP). The DPPH and ABTS, and FRAP and FICA, respectively ranked in ascending order: HRP < ESP < ESS < CSP < CSS, and HRP < ESP < CSP ≤ ESS < CSS. Correlations between DPPH versus total flavonoid content (TFC), ABTS versus total phenolic content (TPC), FRAP versus TPC, and FICA versus condensed tannin content were strong in plain spices. The DPPH against TPC and TFC, ABTS against TFC, FRAP against TFC, and FICA against TPC correlated strongly in both raw and cooked spice mixture products. Spices used for popular Ethiopian spicy hot red pepper powder production, and both raw and cooked mixture of them are promising sources of antioxidants with positive health effects.